Identification of ethyl pyruvate as a NLRP3 inflammasome inhibitor that preserves mitochondrial integrity - Sujun Li; Fang Liang; Kevin Kwan; Yiting Tang; Xiangyu Wang; Youzhou Tang; Jianhua Li; Huan Yang; Sangeeta S. Chavan; Haichao Wang; Ulf Andersson; Ben Lu; et al. (BMC, 2018)
Abstract Background The NLRP3 inflammasome, a cytosolic complex that mediates the maturation of IL-1β and IL-18 as well as the release of high mobility group box 1 (HMGB1), contributes to the lethality of endotoxic shock. Ethyl pyruvate (EP) was previously shown to inhibit HMGB1 release and promote survival during endotoxemia and experimental sepsis. However, the underlying protective mechanism remains elusive. Result EP dose-dependently inhibited the ATP-, nigericin-, alum-, and silica-induced caspase-1 activation and HMGB1 release in mouse macrophages. EP failed to inhibit DNA transfection- or Salmonella Typhimurium-induced caspase-1 activation and HMGB1 release. Mechanistically, EP significantly attenuated mitochondrial damage and cytoplasmic translocation of mitochondrial DNA, a known NLRP3 ligand, without influencing the potassium efflux, the lysosomal rupture or the production of mitochondrial reactive oxygen species (mtROS). Conclusion Ethyl pyruvate acts as a novel NLRP3 inflammasome inhibitor that preserves the integrity of mitochondria during inflammation.